FUT1- and GAL3ST2-mediated cellular glycan remodeling broadly restricts sialic acid–dependent viral infections - Xinyu Zhu; Satoko Nakano; Vishwas N. Rao; Hector A. Miranda; M. Ariel Spurrier; Samantha Skavicus; Zhaochen Luo; Nicholas S. Heaton (Proceedings of the National Academy of Sciences, 2026)
Sialic acid is an abundant terminal glycan found on the surface of almost all mammalian cells and is utilized by many viruses as an attachment factor and/or bona fide receptor. Altering canonical cellular glycosylation can affect the ability of viruses to initiate infections; however, no systematic analysis of the effects of altering expression of glycan “capping” enzymes on viral infection rates has been previously performed. We therefore designed an arrayed CRISPR activation screen that targeted 54 glycosyltransferases known to perform terminal glycan modifications and then examined the susceptibility of 12 different viruses that rely on sialic acid receptors on the resultant cell lines. We identified two glycosyltransferases, fucosyltransferase 1 (FUT1) and galactose-3-O-sulfotransferase 2 (GAL3ST2), as capable of inhibiting a broad range of viruses when upregulated, including influenza viruses, respiroviruses, paramyxoviruses, enteroviruses, and coronaviruses. Lectin and viral particle binding assays revealed that the fucosylation and sulfation mediated by FUT1 and GAL3ST2 reduced availability of cell surface expressed α2-3 and α2-6 sialylation and impaired viral attachment during the initial entry process. Furthermore, through adeno-associated virus delivery, we confirmed the inhibitory effects of FUT1 and GAL3ST2 on influenza viruses in various cell models, including primary differentiated human airway cells. Together, our findings identify FUT1 and GAL3ST2 as host restriction factors and suggest that their therapeutic dysregulation may represent a broad-spectrum antiviral strategy.